TINJAUAN PROSEDUR PEMBELIAN BARANG DI BAGIAN PURCHASING PADA PT. DURACONINDO PRATAMA JAKARTA - Aryadi, Heri; Wahyuni, Wahyuni (Aksara Public, 2020)
Therefore the author conducted a study entitled Review of Purchasing Procedures in the Purchasing Section at PT Duraconindo Pratama Jakarta. The method used in this research is to use a descriptive qualitative method with data collection techniques through observation, namely making direct observations relating to the purchase of goods, interviewing by conducting questions and answers directly by asking questions related to purchasing goods in the purchasing department in order to obtain data and information accurate and documentation that is collecting supplementary data related to the purchase of goods at PT. Duraconindo Pratama Jakarta. Procedure for purchasing goods in the purchasing department at PT. Duraconindo Pratama has several stages, namely receiving a list of requests for goods. supplier selection, submission of requests for price quotes, supplier selection based on quality and price, expenditure on purchase orders. Procedure for purchasing goods in the purchasing department at PT. Duraconindo Pratama is good enough, but there needs to be additional human resources in the finance section and minimizing mistakes in shipping goods that are not in accordance with POs, with coordination between suppliers and factories (warehouses).